The Physicochemical and Organoleptic Quality of Liver Nuggets with Corn Flour and Sago Flour (Faculty of Animal Science Universitas Brawijaya, 2023)
The study aims to determine the effect of using corn flour and sago flour on chicken liver nuggets and beef liver nuggets in terms of physicochemical and organoleptic quality. The materials used in the study were chicken liver, beef liver, sago flour, corn flour, chicken eggs, salt, garlic, pepper, and breadcrumbs. The research method used was a laboratory experiment with a nested Randomized Block Design (RBD) with 4 treatments and 5 replications. The treatment was distinguished by several codes including CC: chicken liver+corn flour, CS: chicken liver+sago flour, BC: beef liver+corn flour, and BS: beef liver + sago flour. The variables analyzed were water content, water activity (Aw), carbohydrates, texture, and organoleptic tests.